The missing beat a study on the religion beat in the Philippine national media - Santos, Eimor Pineda; Chua, Yvonne T.; University of the Philippines Diliman. College of Mass Communication (2013)
"This thesis reveals that in the Philippine national media, there is lack of news on religion and the absence of a religion beat. What is practiced instead is a church beat. The study integrates the Marketplace of Religion theory with McQuail's Mediation of Reality Model to probe into how the national media cover news on religion. It examines what religious issues and events make it to the mainstream and which denominations are being covered. In-depth interviews show what it means to be a church beat reporter in the secular media; how reporters cover the beat and the challenges and ethical dilemmas they face. The study reveals that like in any other beat, biases and corruption can get in the way of the reporters' coverage. The thesis also explores whether it is reasonable and feasible to have a religion beat in the Philippines national media. It recommends ways on how to improve the beat system employed by the media as it aims to improve the practice of Philippine journalism through professional and ethical standards."
Vita.
Thesis (A.B. Journalism)--University of the Philippines Diliman
Keywords: Mass media -- Religious aspects; Journalism, Religious -- Philippines; Religion and the press; Church and the press